Expansión del rango de distribución de Mimosa polycarpa (Fabaceae, caesalpinioideae) hacia el sur - Morales, Matias; Noguera, Justo Maximiliano; Aguirre, G.; Fortunato, Renee Hersilia (Sociedad Argentina de Botánica, 2025)
Poster